THE IMPACT OF TOURISM ON CULTURAL HERITAGE PRESERVATION IN POTOHAR REGION - Mohammad Afnan Haider; Dr. Abid Ghafoor Chaudhry (International Journal of Contemporary Issues in Social Sciences, 2024)
This research investigates the complex relationship between tourism development and cultural heritage preservation in Pakistan's Potohar region. The study used a google form survey aimed at young individuals, a growing demographic of cultural heritage tourists. The findings show that historical relevance, architectural beauty, and religious significance are major motivators for visiting Potohar's cultural heritage sites. However, the research also highlights the possible concerns with the tourist’s experience, emphasizing the need for better infrastructure and responsible tourist actions. The study verifies the strong appreciation for Potohar's cultural heritage and finds potential benefits between tourism and preservation initiatives, with greater awareness and money generation potentially financing restoration operations. However, a balanced approach is necessary. Concerns regarding wear and tear on cultural heritage sites require appropriate tourism practices. The study includes significant recommendations from respondents for attaining this balance, including as government investment in restoration, public education programs, community engagement, and sustainable tourist practices. Additional research into the economic impact of tourism and the viewpoints of many stakeholders is suggested. This study adds to the ongoing effort to safeguard the long-term viability of Potohar's cultural heritage by giving useful data and insights to policymakers, tourist stakeholders, and local people.